Yoruba hometowns : - Trager, Lillian (Lynne Rienner, 2001)
The pattern of migrants maintaining strong ties with their home communities is particularly common in sub-Saharan Africa, where it has important social, cultural, political, and economic implications. This book explores the significance of hometown connections for civil society and local development in Nigeria. Rich ethnographic description and case studies illustrate the links that the Ijesa Yoruba maintain with their communities of origin - links that both help to shape social identity and contribute to local development. Trager also examines indigenous concepts of "development," demonstrating how the Yoruba bring their understandings of development to efforts in their own communities. Placing her work in the context of national political and economic change, she raises questions about the motivations, implications, and consequences of local development efforts, not only for the communities and their members, but also for the larger polity.